Rural-urban differences in prevalence of and risk factors for refractive errors among school children and adolescents aged 6–18 years in Dalian, China - Wang, Yachen; Liu, Lei; Lu, Zhili; Qu, Yiyin; Ren, Xianlong; Wang, Jiaojiao; Lu, Yan; Liang, Wei; Xin, Yue; Zhang, Nan; Jin, Lin; Wang, Lijing; et al. (Frontiers in Public Health, 2022)
Purpose To assess the prevalence of refractive errors (REs) in school children aged 6–18 years in urban and rural settings in Dalian, Northeast of China. Methods This is a school-based cross-sectional survey using multi-stage randomization technique. Six- to eighteen-year-old school children from elementary schools, junior and senior high schools from a rural area and an urban area in Dalian were included in December 2018. All subjects underwent a comprehensive questionnaire and eye examination. Results A total of 4,522 school children with 6–18 years of age were investigated. The age, gender-adjusted prevalence of myopia, and anisometropia were 82.71 and 7.27% among the urban students as compared to 71.76% and 5.41% among the rural ones (OR = 1.80, 95 % CI = 1.53 - 2.11, P < 0.001; OR = 1.29, 95 % CI = 1.00–1.67, P = 0.049), respectively. The hyperopia was less common in urban students than in rural ones (5.63 vs. 10.21%; OR = 0.54, 95 % CI: 0.43–0.67, P < 0.001). However, there was no significant difference in prevalence of astigmatism between urban (46.07%) and rural (44.69%) participants (OR = 0.96, 95 % CI: 0.84–1.10, P = 0.559). The differences on prevalence of REs were attributed to different social-demographic and physiologic factors. Conclusions The students from urban settings are more likely to have myopia and anisometropia but less likely to have hyperopia than their rural counterparts. Although considerable attention had been paid to controlling REs, it is necessary to further consider the urban-rural differences in REs.